Viscosity β- coefficient and thermodynamic parameters for Viscosity flow of some electrolytes During the passage of Alternating curi’ent at different voltages - Mansowi, Saber E.; Hasieb, Ibrahtm H.; Abdul- kariem, Nadhim (Al-Mukhtar Journal of Sciences, 2009)
A total number of 57 birds from commercial broiler strain (30 males and 27 females) were used to investigate the influence of age and sex on dressing percentage and its relation to tibia length in commercial broiler. The results of this study showed that no significant differences between males and females in all studied traits , but the overall means were higher in males than in females except dressing percentage and tibia length. The age was significantly affect (p<0.05) the dressing percentage, but not the tibia length, while the weight increased with advanced age. The correlation coefficient between body live-weight and experimental traits was high and positive in both sex, but dressing percentage decreased with age at 40 and 58 days in males. Meanwhile, correlation coefficient was highly positive between tibia length and the studied traits in both sexes but it was negative in females aged 40 days. From this study, it was concluded that, there is a relationship between tibia length and the studied traits specially in males , however further work is needed.